Orai Application in Teaching Speaking - Pujiani, Ayu Puspa; Rizkiani, Siska (IKIP Siliwangi, 2025)
Learning in the 4.0 era was the era of ICT (Information and Communication Technology) that made students are familiar with various applications which allow them to get more varied. Thus, it is necessary to select media and facilitate teachers and learners in the speaking activities. Either of the applications used to help to learn is the ORAI application. The aim of this research is to explore the ORAI application in teaching speaking on self-introduction material for the English learner to be preferable English speakers in a delight way. The researchers use a qualitative descriptive method to examine and find out responses the student toward the ORAI Application in speaking. The subject was 7th-grade students in one of the junior high schools in Cimahi 2021/2022 academic years consisted of 15 male students. Test, interview, and observation sheet then the data were elaborate by using triangulation. The implementation of the ORAI can assist students in speaking self-introduction easier. The students felt excited and regarded learning self-introduction using the ORAI application as more enjoyable. On the other side, this application takes a lot of time although it can motivate students in learning to speak learning self-introduction.